Education Level of The Board of Directors and Financial Performance of Go Public Banks at The Indonesia Stock Exchange - Muhammad Madyan; Rayindha Galuh Setyowati; Wulan Rahmadani Setiawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Having experience, knowledge, and expertise in banking is important for the board of directors to properly manage its activities, which is indicated by their financial performance. This study investigates the effect of the formal education level of the board of directors on financial performance in terms of profitability. The sample used in this study was 31 banking companies, especially conventional commercial banks listed on the Indonesia Stock Exchange in 2009-2018, with 244 observations. This study uses multiple linear regression analysis with the Ordinary Least Square (OLS) approach. In this study, the dependent variables used are Return On Assets (ROA) and Net Interest Margin (NIM). The independent variables used are the level of education of the board of directors divided into Master and Ph.D. This study indicates that the board of directors with the highest educational level of Masters and Ph.D has a significant positive effect on ROA. Meanwhile, the board of directors with the and education level of Masters has a significant negative effect, and the board of directors with the highest education level of Ph.D has a significant positive effect on NIM.